The Competitiveness of Polish Industrial Goods Exports to the Visegrad Group Countries and the Economic Coherence of the Group - Szymanik, Ewa (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article examines the competitiveness of the export of Polish industrial goods to the countries of the Visegrad Group. Competitiveness was analysed using the main indicators RCA, IIT and export shares. Given the possibility for expanded trade within the group, this issue is important. The research was done to show the opportunity which the coherence of export presents. The conclusions confirm that there are indeed opportunities, but infrastructural barriers must be overcome and an effort must be made to exchange experience gained from improving competitiveness. These measures could boost competitiveness for all because every member of the Group had the same initial terms, but their different approaches to development have yielded different economic results.